1.
2.
3.
4.
5.
_<0, \\ (x+1)^2\geq0, 4x^>_<0, x^>_<0, \\ x\in(0;+\infty), y>0, \\ x\in(-\infty;0), y<0; \\ " alt="\frac{4x}{(x+1)^2}^>_<0, \\ (x+1)^2\geq0, 4x^>_<0, x^>_<0, \\ x\in(0;+\infty), y>0, \\ x\in(-\infty;0), y<0; \\ " align="absmiddle" class="latex-formula">
6.
_<0, \frac{4-4x}{(x+1)^3}^>_<0, \\ -4(x-1)(x+1)^3^>_<0, \\ x\in(-\infty;-1), y'<0, y\searrow, \\ x\in(-1;1), y'>0, y\nearrow, \\ x\in(1;+\infty), y'<0, y\searrow; \\ " alt="y'=(\frac{4x}{(x+1)^2})'=\frac{4(x+1)^2-4x\cdot2(x+1)}{(x+1)^4}=\frac{(x+1)(4x+4-8x)}{(x+1)^4}=\frac{4-4x}{(x+1)^3}, \\ y'=0, \frac{4-4x}{(x+1)^3}=0, \\ (x+1)^3\neq0, x\neq-1, \\ 4-4x=0, -4x=-4, x=1; \\ y'^>_<0, \frac{4-4x}{(x+1)^3}^>_<0, \\ -4(x-1)(x+1)^3^>_<0, \\ x\in(-\infty;-1), y'<0, y\searrow, \\ x\in(-1;1), y'>0, y\nearrow, \\ x\in(1;+\infty), y'<0, y\searrow; \\ " align="absmiddle" class="latex-formula">
7.